Oxford Handbooks Online 2013
DOI: 10.1093/oxfordhb/9780199589074.013.0007
|View full text |Cite
|
Sign up to set email alerts
|

Digital Inequality

Abstract: This chapter investigates the research on inequalities in society, and also considers the digital inequality beyond overly simplistic conceptions of access to technologies. Additionally, it describes how people's background characteristics relate to their web-use skills and what they do online. The social implications of differentiated Internet uses are covered. The theoretical perspectives presented point out various forms of inequality associated with information and communications technology (ICT) uses, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 0 publications
1
44
0
5
Order By: Relevance
“…While the reader may find it ironic that a study critiquing projects with much larger samples, hundreds of thousands or even millions of observations, draws on just a few hundred cases that are not a random sample of the national population, it is an especially relevant sample here. the group is homogeneous on age and education, two variables that research has identified as important correlates of Internet use (Hargittai and Hsieh 2013), suggesting that this demographic is among the most active of online participants. the data from this young, wired, educated group allow me to investigate other factors relevant to SNS selection and how those choices change over time.…”
Section: Sns Adoption Among a Diverse Group Of Young Adultsmentioning
confidence: 95%
“…While the reader may find it ironic that a study critiquing projects with much larger samples, hundreds of thousands or even millions of observations, draws on just a few hundred cases that are not a random sample of the national population, it is an especially relevant sample here. the group is homogeneous on age and education, two variables that research has identified as important correlates of Internet use (Hargittai and Hsieh 2013), suggesting that this demographic is among the most active of online participants. the data from this young, wired, educated group allow me to investigate other factors relevant to SNS selection and how those choices change over time.…”
Section: Sns Adoption Among a Diverse Group Of Young Adultsmentioning
confidence: 95%
“…Though such cohort studies offer important findings about patient use and perceptions of health IT, they do not tell us enough about the views of the population overall. Perceptions of the value of EHRs by some groups and not others may lead to different usage patterns that can cause inequality in the resources and skills created by technology use, i.e., the so-called "second-level digital divide" [30][31] , which can exacerbate existing health disparities.…”
Section: Resultsmentioning
confidence: 99%
“…Согласно данным большого исследования, проведенно-го в рамках Pew Internet & American Life Project, наиболее точными предикторами интенсивности и экстенсивности пользования Интернетом 4 являются уровни до-хода и образования . Теоретически существует три варианта эффектов воздействия распростране-ния и использования Интернета на социальное неравенство (Hargittai, Hsieh, 2013). В случае если Интернет распространен преимущественно среди верхних слоев общества, то социальное неравенство и исключение усугубляются; такая модель социального эффекта называется «богатый становится богаче».…”
Section: интернет и социальное неравенство: «цифровые разрывы»unclassified